Validation of electronic visual acuity (EVA) measurement against standardised ETDRS charts in patients with visual field loss from inherited retinal degenerations - Jolly, J; Juenemann, K; Boagey, H; Nadsady, M; Bridge, H; Maclaren, R (BMJ Publishing Group, 2019)
Background With the increase in clinical trials testing therapy for retinal disease, there is a need to ensure that outcome measures are both accurate and standardised. The US Food and Drug Administration favours the use of visual acuity measured using ETDRS logMAR charts. The loss of visual field can interfere with visual tracking across the charts, leading to increased variability of measurements. Electronic visual acuity (EVA) presents the optotype on the centre of a screen, thereby removing the tracking element of the task, and may provide a more precise measurement. Methods Visual acuity was measured twice using ETDRS charts, EVA automated single letter (E-ETDRS) and EVA single line (EVA-SL) presentation (EMMES). Patients underwent microperimetry (MAIA; Centervue) to determine visual field. We tested 65 patients with rod-cone dystrophies and 41 healthy volunteers. Results Both participant groups read 2–3 letters more on average on the electronic charts compared with ETDRS. Limits of agreement using a modified Bland-Altman analysis account for replicates were wider in eyes with foveal defects (−9 to 18) compared with eyes without foveal defects (−11 to 15). Electronic charts in the presence of foveal defects reduced the range (−11 to 13). Conclusion EVA may provide more accurate measures of visual acuity than traditional ETDRS charts in patients when the visual field loss encroached on the central vision. Electronic presentation with a single line of letters was the favoured style reported by patients and should be considered in future interventional clinical trials.